1994
DOI: 10.1111/j.1365-2702.1994.tb00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐operative pain management: a literature review

Abstract: The appropriateness of any set of criteria generated to measure the quality of a particular intervention is dependent upon a thorough, up-to-date assessment of the current state-of-the-art. Few areas in nursing have received as much research attention as that of pain control, particularly post-operative pain control. The following review of the literature* on this subject complements earlier reviews undertaken by Seers (1988) by organizing the information according to four distinct categories, namely environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Lower limb fracture nolol medication. Propranolol is known to induce fatigue, insomnia, depression and hypotension as a direct consequence of beta-adrenergic receptor blockade (Govoni & Hayes 1990, Jordan & Torrance 1995, Hoffman & Lefkowitz 1996, British National Formulary 1997 While our respondents felt that the personal attributes of their nurses strengthened their psychological coping mechanisms, closer observation of symptoms and side effects would have pre-empted much of the pain, nausea and fatigue described here (Holmes & Eburn 1989, Kitson 1994. Patients most appreciate practical help in minimizing stress and strengthening coping mechanisms (Larson 1984, Mayer 1987, Cochran & Ganong 1989, Von Essen & Sjoden 1991a, 1991b.…”
Section: Issues and Innovations In Nursing Practicementioning
confidence: 83%
“…Lower limb fracture nolol medication. Propranolol is known to induce fatigue, insomnia, depression and hypotension as a direct consequence of beta-adrenergic receptor blockade (Govoni & Hayes 1990, Jordan & Torrance 1995, Hoffman & Lefkowitz 1996, British National Formulary 1997 While our respondents felt that the personal attributes of their nurses strengthened their psychological coping mechanisms, closer observation of symptoms and side effects would have pre-empted much of the pain, nausea and fatigue described here (Holmes & Eburn 1989, Kitson 1994. Patients most appreciate practical help in minimizing stress and strengthening coping mechanisms (Larson 1984, Mayer 1987, Cochran & Ganong 1989, Von Essen & Sjoden 1991a, 1991b.…”
Section: Issues and Innovations In Nursing Practicementioning
confidence: 83%
“…Many even recommend that this process be formalized through the use of assessment tools. However, and despite an abundance of studies that have explored factors affecting nurses’ pain assessment and analgesic decisions (Harrison 1991, Kitson 1994, Allcock 1996), no study has explored directly why nurses decide not to ask patients about their pain. Furthermore, published studies have not explored the interplay between barriers posed by nurses themselves (ones they may not be aware of), and those added by the ward setting and policies, within which they practise (barriers nurses are likely to recognize).…”
Section: Introductionmentioning
confidence: 99%
“…In surveys of surgical patients, it has been found that approximately half of all hospitalized postoperative patients failed to receive adequate pain relief ( Jacox, Ferrell, Heidrich, Hester, & Miaskowski, 1992;Jurf & Nirschl, 1993). Patients reporting moderate to high levels of pain received less than half of the pain medication that was ordered (Kitson, 1994;Tittle & McMillan, 1994). This underutilization of prescribed medications may be related to the fact that health care professionals often evaluated pain at lower levels than patients re-ported and used objective symptoms rather than the patient's self-report to assess the patient's pain (Bowman, 1994;Mateo & Krenzischek, 1992;Olden, Jordan, Sakima, & Grass, 1995;Paice, Mahon, & Faut-Callahan, 1995;Stephenson, 1994;Webb & Kennedy, 1994;Zalon, 1993).…”
mentioning
confidence: 99%